THE CHARACTERISTICS, MODE OF DELIVERY OF PRIMIGRAVIDA PREGNANT WOMEN AND RELATED FACTORS AT BINH THUAN GENERAL HOSPITAL: A DESCRIPTIVE AND ANALYTICAL CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2026)
Background: Primipara pregnancy have specific characteristics that require attention during pregnancy and labor. Studying the clinical characteristics, methods of pregnancy termination, and related factors in primiparous women will help physicians make appropriate recommendations for each specific case to reduce obstetric complications.Objectives: 1. To describe the characteristics of primiparous women. 2. To determine the rate of cesarean section and related factors.Materials and method: Descriptive and analytical cross-sectional study, All primiparous women, full-term, admitted to and terminated at the Obstetrics Department of Binh Thuan General Hospital.Results: The average age was 23.8 years. The majority had a normal body mass index (56%), with a higher proportion of overweight and obese pregnant women compared to underweight pregnant women (23% versus 21%). Of the pregnant women who underwent GBS testing (71%), the positive rate was 15.5%. The rate of cesarean section was higher than vaginal delivery (57% vs. 43%). Pregnant women ≥ 35 years old tended to have a higher rate of cesarean section than primiparous women under 35 years old (OR = 3.17); however, the difference was not statistically significant (p = 0.387). The group with BMI ≥ 23 had a higher likelihood of cesarean section than the group with BMI < 23.Conclusion: Primipara pregnancy have a higher rate of cesarean section than vaginal delivery, especially those ≥ 35 years old.
Keywords: primiparous, older primiparous, cesarean section, obesity.